1990
DOI: 10.1111/j.1748-1716.1990.tb08953.x
|View full text |Cite
|
Sign up to set email alerts
|

Resumption of rat oocyte meiosis is paralleled by a decrease in guanosine 3‘,5’‐cyclic monophosphate (cGMP) and is inhibited by microinjection of cGMP

Abstract: The aim of the present study was to measure the level of cyclic GMP (cGMP) compared with the level of cyclic AMP (cAMP) in rat oocytes during resumption of meiosis I (oocyte maturation) and to microinject these cyclic nucleotides into the oocyte to study their effects on oocyte maturation. Immature oocytes were obtained from prepubertal rats primed with pregnant mare's serum gonadotropin. OOcytes were isolated adn short-term cultured under conditions enabling spontaneous maturation. The levels of cGMP and cAMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 26 publications
3
68
0
3
Order By: Relevance
“…However, because cAMP levels fall early in oocyte maturation (Schultz et al 1983a, Tö rnell et al 1990, Conti et al 2002, it seems more likely that the targets for such a meiosis-inducing substance are upstream of cAMP. There are several possible targets on which a meiosis-inducing factor could act within the oocyte (see Fig.…”
Section: How Does Lh Trigger Meiotic Resumption?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, because cAMP levels fall early in oocyte maturation (Schultz et al 1983a, Tö rnell et al 1990, Conti et al 2002, it seems more likely that the targets for such a meiosis-inducing substance are upstream of cAMP. There are several possible targets on which a meiosis-inducing factor could act within the oocyte (see Fig.…”
Section: How Does Lh Trigger Meiotic Resumption?mentioning
confidence: 99%
“…Spontaneous maturation of oocytes isolated from their follicles can be prevented by including membrane permeant cAMP analogs or cAMP phosphodiesterase inhibitors, such as hypoxanthine or 3-isobutyl-1-methylxanthine (IBMX), in the culture medium (Cho et al 1974, Dekel & Beers 1978, Conti et al 2002. Moreover, cAMP levels decrease in oocytes following removal from their follicles (Tö rnell et al 1990), as well as in isolated oocytes after removal of IBMX (Schultz et al 1983a, Vivarelli et al 1983. The decrease in oocyte cAMP occurs within 2 h after washing out IBMX, a time during which the oocyte becomes committed to resuming meiosis (Schultz et al 1983a, Vivarelli et al 1983.…”
Section: Maintenance Of Meiotic Arrestmentioning
confidence: 99%
“…smooth muscle cells, platelets or endothelial cells), numerous NO-effects are mediated by soluble guanylate cyclase (sGC) and by the synthesis of cyclic guanosine monophosphate (cGMP) (Murad, 1994;Friebe and Koesling, 2003). sGC and cGMP also play an important role in the ovary (Grasselli et al, 2001;LaPolt et al, 2003;Shi et al, 2004) and it was proved that they are also involved in the regulation of meiosis (Tornell et al, 1984(Tornell et al, , 1990. Petr et al (2006) demonstrated that the activation of in vitro matured pig oocytes via the NO-dependent signalling pathway was mediated through cGMP.…”
Section: Which Processes Are Specific To No-induced Oocyte Activation?mentioning
confidence: 99%
“…Is the cGMP pathway as involved in the control of bovine oocyte meiosis as it is in rodent oocytes? The cGMP analog 8-bromo-cGMP as well as the guanylate cyclase stimulators atrial natriuretic peptide and protoporphyrin 1X did not have any effect on bovine oocyte meiosis after 7h of culture (Bilodeau-Goeseels, 2007), while cGMP derivatives inhibited spontaneous nuclear maturation in rat denuded oocytes (Törnell et al, 1990). The cGMP pathway can also be activated by nitric oxide (NO), which is synthesized by NO synthase (NOS) and activates soluble cytoplasmic guanylate cyclase.…”
Section: Other Signalling Pathways Involved In the Control Of Bovine mentioning
confidence: 99%
“…This brings us back to the original hypothesis that cAMP from somatic cells is transferred to the oocyte and inhibits meiosis. However, because the major oocyte phosphodiesterase is PDE3A (Masciarelli et al, 2004) which is inhibited by cyclic guanosine monophosphate (cGMP), and various studies showed that cGMP could be involved in meiotic arrest (Sela-Abramovich et al, 2008;Törnell et al, 1990), it was hypothesized that cGMP from the somatic cells could reach the oocyte through gap junctions, inhibit PDE3A and maintain meiotic arrest. Using Förster resonance energy transfer-based cyclic nucleotide sensors in follicle-enclosed oocytes, Norris et al (2009) showed that cGMP does pass through gap junctions into the oocyte to contribute to the maintenance of high cAMP levels by inhibiting PDE3A.…”
Section: If the Signal From Follicle Cells To Inhibit Meiosis Is Not mentioning
confidence: 99%